Cannabis sativa: Much more beyond Δ9-tetrahydrocannabinol. (July 2020) - Alves, Patrícia; Amaral, Cristina; Teixeira, Natércia; Correia-da-Silva, Georgina
Graphical abstract: Highlights: Cannabidiol (CBD) and cannabidivarin (CBDV) are cannabinoids with therapeutic potential. CBD has anti-inflammatory, anti-convulsive, neuroprotective and anti-tumour actions. CBDV presents anti-epileptic and anti-inflammatory known properties. CBD and CBDV act on different molecular targets, such as receptors and enzymes. Besides its therapeutic potential, exposure to CBD and CBDV may have associated risks. Abstract: Cannabis is the most used illicit drug worldwide and its medicinal use is under discussion, being regulated in several countries. However, the psychotropic effects of Δ 9 -tetrahydrocannabinol (THC), the main psychoactive compound of Cannabis sativa, are of concern. Thus, the interest in the isolated constituents without psychotropic activity, such as cannabidiol (CBD) and cannabidivarin (CBDV) is growing. CBD and CBDV are lipophilic molecules with poor oral bioavailability and are mainly metabolized by cytochrome P450 (CYP450) enzymes. The pharmacodynamics of CBD is the best explored, being able to interact with diverse molecular targets, like cannabinoid receptors, G protein-coupled receptor-55, transient receptor potential vanilloid 1 channel and peroxisome proliferator-activated receptor-γ. Considering the therapeutic potential, several clinical trials are underway to study the efficacy of CBD and CBDV in different pathologies, such as neurodegenerative diseases, epilepsy, autism spectrum disorders and pain conditions. The anti-cancer properties of CBD have also been demonstrated by several pre-clinical studies in different types of tumour cells. Although less studied, CBDV, a structural analogue of CBD, is receiving attention in the last years. CBDV exhibits anticonvulsant properties and, currently, clinical trials are underway for the treatment of autism spectrum disorders. Despite the benefits of these phytocannabinoids, it is important to highlight their potential interference with relevant physiologic mechanisms. In fact, CBD interactions with CYP450 enzymes and with drug efflux transporters may have serious consequences when co-administered with other drugs. This review summarizes the therapeutic advances of CBD and CBDV and explores some aspects of their pharmacokinetics, pharmacodynamics and possible interactions. Moreover, it also highlights the therapeutic potential of CBD and CBDV in several medical conditions and clinical applications.